The Relationship Between the Teaching Goal Orientations and Teaching Approach of Physical Education and Sports Teachers - Veysel Sarıgül,; Yunus Emre Karakaya,; Uğur İnce,; Cemal Yalçın, (Journal of Educational Issues, 2024)
This study was conducted in line with the opinions of physical education and sports teachers working in educational institutions to reveal the relationship between goal orientation towards teaching and teaching approaches. A total of 279 physical education and sports teachers from different schools in Elazig were enrolled in the study. To determine the target orientation of the research group towards teaching ‘Goal Orientation Scale for Teaching’ and to determine the teaching approaches ‘Instructional Approaches Inventory’ were used. The data obtained are saved by using the licensed SPSS 22.0 package program. ‘One Way Analysis of Variance (ANOVA)’ and ‘Pearson Correlation Analysis’ has been made. As a result of the correlation analysis, a positive and high-level relationship between ‘Goal Orientation Scale for Teaching’ and ‘Skill Approach’ has been found (r = 0.789; p = 0.000). It has been concluded that there was a very high positive correlation between the ‘Teaching Approaches Inventory Scale’ and ‘Developmental’ subscale (r = 0.932; p = 0.000). The relationship between goal orientations towards teaching and teaching approaches was found to be positive and moderate (r = 0.616; p = 0.000). The fact that physical education and sports teachers enrich their teaching by establishing a relationship between their goal orientations and teaching approaches towards teaching in the lesson process will further contribute to students’ learning physical education and sports lessons in a meaningful way.